Construcción de un modelo multinivel para el análisis de la agresividad indirecta en escolares; comuna nororiental, Medellín, Colombia, 2001 (2004)
ABSTRACT: Tendencies in current epidemiology that have linked the relationship between health and illness with the social context of individuals are exposed, using contemporary statistical methodologies as those of the hierarchical models. Some characteristics of multilevel model are also presented, as well as types of these and their appropriateness in comparison with other existing models frequently used in epidemiology, especially for data analysis with hierarchical structure. In addition, fundamental objectives of this statistical analysis and their importance in epidemiology are described. Finally, the way in which this technique functions is explained, showing its use in epidemiological studies through an application in the analysis of reactive aggression symptoms with children. Data source of test COPRAG was taken from scholars in a suburb of the northeastern area of Medellín, Colombia in 2001.